Daughterless, the Drosophila orthologue of TCF4, is required for associative learning and maintenance of the synaptic proteome - Laura Tamberg; Mariliis Jaago; Kristi Säälik; Alex Sirp; Jürgen Tuvikene; Anastassia Shubina; Carl Sander Kiir; Kaja Nurm; Mari Sepp; Tõnis Timmusk; Mari Palgi (The Company of Biologists, 2020)
Mammalian transcription factor 4 (TCF4) has been linked to schizophrenia and intellectual disabilities, such as Pitt-Hopkins syndrome (PTHS). Here, we show that similarly to mammalian TCF4, fruit fly orthologue Daughterless (Da) is expressed widely in the Drosophila brain. Furthermore, silencing of da, using several central nervous system-specific Gal4 driver lines, impairs appetitive associative learning of the larvae and leads to decreased levels of the synaptic proteins Synapsin (Syn) and Discs large 1 (Dlg1), suggesting the involvement of Da in memory formation. Here, we demonstrate that Syn and dlg1 are direct target genes of Da in adult Drosophila heads, as Da binds to the regulatory regions of these genes and the modulation of Da levels alter the levels of Syn and dlg1 mRNA. Silencing of da also affects negative geotaxis of the adult flies, suggesting the impairment of locomotor function. Overall, our findings suggest that Da regulates Drosophila larval memory and adult negative geotaxis, possibly via its synaptic target genes Syn and dlg1. These behavioural phenotypes can be further used as a PTHS model to screen for therapeutics. This article has an associated First Person interview with the first author of the paper.